2020
DOI: 10.21037/jtd.2019.12.83
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality prediction algorithms for patients undergoing primary percutaneous coronary intervention

Abstract: Mortality risk of ST-segment elevation myocardial infarction (STEMI) patients shows high variability. In order to assess individual risk, a number of scoring systems have been developed and validated.Yet, as treatment approaches evolve over time with improving outcomes, there is a need to build new risk prediction algorithms to maintain/increase prognostic accuracy. One of the most relevant improvements of therapy is primary percutaneous coronary intervention (PCI). We overview the characteristics and discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The CADILLAC risk score was developed from a cohort of STEMI patients undergoing primary PCI [10] . Among various risk models, the CADILLAC score is well-balanced because it includes presentation characteristics, procedural data, and laboratory and imaging results [22] . Recently, Mitarai et al reported the good predictivity of "angiographic GRACE score" for inhospital mortality, which incorporates a location of culprit artery and TIMI flow grade in addition to the original GRACE risk score [25] , suggesting the importance of other information than presentation characteristics in risk stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CADILLAC risk score was developed from a cohort of STEMI patients undergoing primary PCI [10] . Among various risk models, the CADILLAC score is well-balanced because it includes presentation characteristics, procedural data, and laboratory and imaging results [22] . Recently, Mitarai et al reported the good predictivity of "angiographic GRACE score" for inhospital mortality, which incorporates a location of culprit artery and TIMI flow grade in addition to the original GRACE risk score [25] , suggesting the importance of other information than presentation characteristics in risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we exclusively tested the CADILLAC and GRACE risk scores. Thus, the impact of different risk models such as TIMI and Zwolle risk scores which are not suitable to our dataset is unknown [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Various algorithms have been developed to predict in-hospital outcomes. These include mortality prediction systems, such as the acute physiology and chronic health evaluation (APACHE) score, the simplified acute physiology score (SAPS), and the sequential organ failure assessment (SOFA) score [ 5 , 6 , 7 , 8 , 9 ], the duration of stay estimation based on electronic health record data [ 10 ], and outcomes prediction-specific to underlying medical conditions [ 11 , 12 ]. However, these algorithms are tailored for subjects admitted to the intensive care units or general medical emergency departments and are not optimized to predict outcomes at the time of admission to the cardiac care unit.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they may contribute to an improved quality of care. Furthermore, risk models may be helpful in clinical trial design identifying patients with the needed risk profile thereby increasing statistical power or reducing sample size and costs [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, 30-day risk-adjusted mortality is one of the quality indicators that is used to evaluate quality of care of STEMI patients [ 3 ]. As in many of the current risk estimation algorithms, heart rate and systolic blood pressure are key predictors of the GRACE 2.0 score [ 1 ]. Nevertheless, these parameters may also be altered by the applied medical treatment / circulatory support without concomitant improvement in microcirculatory failure / prognosis of the patient.…”
Section: Introductionmentioning
confidence: 99%